Tota knee replacement in Tobruk Medical Center in, Libya (Albayan Scientific Journal, 2023)
The aim of this study to investigate about the causes that lead to total  knee joint replacement operation, especially the operation that is performed in Medical Tobruk Center where there are many reasons that cause problem in Knee joint. And the knee joint ,which is one of the largest and most complex joints in the human body.There are many reasons that the doctor may resort to implanting the joint for the patient, such as obesity, osteoarthritis and old age. As we have looked at this study for the most common reasons found in Tobruk.In this study we will discuss the structure of the knee joint and the structures surrounding it from the muscles, ligaments, nerves and bones.Then diagnosed patients and follow them after the operation to observe any complications that may occur after the surgery  and also rehabilitate them by physical therapy to recover in the least time to reduce any complication and gone back to normal daily activity.  Whereas information were collected about the cases of the orthopedics department in Medical Tobruk Center, it has been found 25 Total knee Replacements performed  between Aug, 2019 to Dec, 2019, as result to workshop that did in that period. It has been found cases with different reason that led to knee replacement such as osteoarthritis. In addition to, the most The patients were at  old age over 50 years old.  Cases had followed up after operation were 7.Keywords: Total knee Rreplacement, Tobruk Medical Centre,Libya, 2019.
Keywords: Total knee Rreplacement; Tobruk Medical; Centre; Libya; 2019